IMPLEMENTASI SIKLUS DEMINGS PADA PRODUKSI GOOGLE ADS STOCK WARS TRADING COMPETITION DI PT SUCOR SEKURITAS - Izzah, Husna Nurul; Suwanda, Bayu Suriaatmaja; Ernawati, Erna (JURNAL KAJIAN ISLAM MODERN, 2024)
Stock Wars Trading Competition is a trading competition held by PT Sucor Sekuritas since 2019. Stock Wars Trading Competition chose Google Ads as a medium to promote the competition. PDCA (Plan, Do, Check and Action) or what is usually called the Demings cycle, is a cycle of continuous or continuous process improvement. Google Ads Stock Wars Trading Competition uses the Demings cycle in its production process so that advertisements can continue to improve both in terms of ad quality and audience. The purpose of writing this journal is to analyze the implementation of the Demings cycle in the production of the Google Ads Stock Wars Trading Competition. The data collection techniques used were active participation, interviews, observation and literature study. The results of observations while carrying out final project activities at PT Sucor Sekuritas are that each stage in the PDCA cycle has its own Google Ads production stage. The Plan stage includes writing headlines, writing descriptions, creating campaign posters, selecting low-competition keywords, demographic targeting, location targeting, and audience targeting. The do stage consists of setting the advertising schedule and determining the campaign budget. The check stage includes daily monitoring and recording of the published Google Ads Stock Wars Trading Competition. The final action stage is publishing the Google Ads that have been produced.